(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
OBJECTIVE: To estimate patient and health care delays in the diagnosis of PTB and to evaluate associated factors. METHODS: PTB incident cases ≥18 years diagnosed between September 2010 and September 2011 in the Lazio region; information on symptoms and date of onset, health professionals contacts, diagnostic exams performed, and drugs prescribed before diagnosis were collected through a standardized questionnaire. The total delay (TD) was divided into patient delay (PD: from symptoms onset to first contact with healthcare services) and health system delay (HSD: from first contact to diagnosis). RESULTS: 278 cases were evaluated. Median PD,HSD, and TD, were 31, 15, and 77.5 days, respectively. The median PD, HSD, and TD were significantly lower in foreign born patients (26, 10.5, 63.5, vs. 45, 36, 100 days, respectively). Other factors independently associated with longer delay were: absence of fever and presence of weight loss for PD; prior unspecific treatment, absence of cough, consult with a general practitioner, visit to an outpatient clinic, and a PD <30 days for HSD. CONCLUSIONS: In Italy, the delay in TB diagnosis is similar to that estimated in other European countries. Results indicate that actions aimed to reduce diagnostic delay should be primarily addressed to Italian patients.